Extraction of high-molecular-weight genomic DNA for long-read sequencing of single molecules - Baptiste Mayjonade; Jérôme Gouzy; Cécile Donnadieu; Nicolas Pouilly; William Marande; Caroline Callot; Nicolas Langlade; Stéphane Muños (BioTechniques)
De novo sequencing of complex genomes is one of the main challenges for researchers seeking high-quality reference sequences. Many de novo assemblies are based on short reads, producing fragmented genome sequences. Third-generation sequencing, with read lengths >10 kb, will improve the assembly of complex genomes, but these techniques require high-molecular-weight genomic DNA (gDNA), and gDNA extraction protocols used for obtaining smaller fragments for short-read sequencing are not suitable for this purpose. Methods of preparing gDNA for bacterial artificial chromosome (BAC) libraries could be adapted, but these approaches are time-consuming, and commercial kits for these methods are expensive. Here, we present a protocol for rapid, inexpensive extraction of high-molecular-weight gDNA from bacteria, plants, and animals. Our technique was validated using sunflower leaf samples, producing a mean read length of 12.6 kb and a maximum read length of 80 kb.